In Silico Analysis of the Effectiveness of α-glucosidase Inhibitors (AGIs) on Phaseolus vulgaris L. as Antidiabetic Agents - Ainun Anugrah; Nur Aini; Salsabila Najah; Siti Sainidah; Yoravika Dwiwibangga; Alfi Tsuraya; Nia Kurnawan; Fatchiyah Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2022)
Diabetes mellitus is a metabolic disorder characterized by high blood sugar levels accompanied by impaired carbohydrate, lipid, and protein metabolism. Alpha-glucosidase inhibitor is an agent that can inhibits the action of the α-glucosidase enzyme, but the synthetic α-glucosidase inhibitors caused various side effects, therefore the search for AGI from natural active compounds is needed. The objective of this study was to determine the effectiveness of the active compound α-glucosidase inhibitor contained in Phaseolus vulgaris as an antidiabetic agent by in silico methods. Flavonoid compounds such as rutin, isoquercitrin, hyperoside, isorhamnetin-3-glucoside, and acarbose (control), were downloaded from the NCBI PubChem database. Human α-glucosidase (PDB ID: 5KZW) 3D structure was obtained from RCSB PDB. Bioactivity predicted using PASSOnline. ADMET and Drug-Likeness with SwissADME and ProTox II. Molecular docking was conducted using HEX 8.0 and visualized with Discovery Studio. This study showed that all of these compounds have sites that interact with the active sites of the α-glucosidase enzyme, and have several similarities compared to acarbose. All compounds have good potential as α-glucosidase inhibitors.  Isorhamnetin-3-glucosidase is the most potential characteristic as an α-glucosidase inhibitor. It has amino acid residues HIS717 (hydrogen), TYR360 (hydrogen and hydrophobic), and ARG608 (hydrogen) which shows higher number of residues in common with acarbose and active sites that also shows fairly high stability. Based on ADME prediction, Isorhamnetin-3-glucoside most likely has the best characteristics based on LogS, %Abs, and also LogKp compared to the other compounds, and has much higher %Abs (40%) than acarbose (-1,8%). It even only has 2 violations of Lipinski rules compared to acarbose that has 3 violations. Thus, overall flavonoid group compounds in P. vulgaris, especially have good potential as a glucosidase inhibitors as antidiabetic agents.